Evaluation of the Effect of Education based on Pender Health Promotion Model on Self- efficacy and Quality of Life in Patients with Leukemia Referred to the Clinics of Shiraz University of Medical Sciences - Zeydani, Maryam; Ghodsbin , Fariba; Keshtkaran, Zahra (International Journal of Psychosocial Rehabilitation, 2020)
Introduction & Objective: Leukemia as a disease can reduce the quality of life and self-efficacy of patients. Educational program as a part of the care program leads to health-promoting behaviors. Thus, this research was conducted with the aim of evaluating the effect of education based on Pender Health Promotion Model on self-efficacy and quality of life in patients with Leukemia. Methods: This is a quasi-experimental interventional study conducted on 54 patients with Leukemia. Data were collected using four questionnaires, Demographic Information Questionnaire, Pender Health Promotion Model Components Questionnaire, Self-efficacy Questionnaire, and Quality of Life Questionnaire. After collecting the data, they were analyzed in SPSS24 software using descriptive statistics, mean, standard deviation, frequency and paired t-test, Pearson correlation coefficient, repeated measure, chi-square, and ANOVA tests. Results: The research results revealed that the score of self-efficacy and quality of life increased significantly (p <0.001) immediately after and one month after education compared to before intervention (p <0.001). In addition, in the intervention group, there was a direct and significant relationship between quality of life and self-efficacy scores immediately and one month after the intervention and Pender health promotion scores immediately and one month after the intervention (P <0.05). Conclusion: The research results suggested that the use of educational intervention based on Pender health promotion model can improve the self-efficacy of patients with regard to self-care behaviors and improve the quality of life in patients with Leukemia.